Comparison of the Use of Discourse Markers in English Speeches between Non-Native and Native Speakers of English - Yulita, Eva; Rukmini, Dwi; Widhiyanto, Widhiyanto (Universitas Negeri Semarang, 2021)
This study revealed the comparison of the use of discourse markers in English speeches between non-native and native speakers of English. The study focused on the types of discourse markers, the similarities and the differences between non-native and native speakers in using discourse markers. This study employed a qualitative research design with the data from the spoken discourse. The findings of the study showed that there were ten sub-categories of discourse markers that are practiced by non-native speakers, namely: assessment marker, manner of a speaking marker, evidential markers, hearsay markers, contrastive discourse markers, elaborative discourse markers, inferential discourse markers, discourse management markers, topic orientation markers, and attention markers. On the contrary, there were nine sub-categories of discourse markers that existed in English speeches, especially delivered by the native speakers such as assessment marker, manner of a speaking marker, evidential markers, hearsay markers, contrastive discourse markers, elaborative discourse markers, inferential discourse markers, topic orientation markers, and attention markers. The total of discourse markers produced by the non-native speakers was 301 utterances while native speakers of English were 269 utterances. Therefore, it is concluded that discourse markers were useful in English speeches either by non-native speakers or native speakers